Pengaruh Konseling Pendidikan terhadap Peningkatan Prestasi Akademik Siswa Slow Learner - Rizka Lailatul Qodaria; Nova Estu Harsiwi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research aims to analyze the effect of educational counseling on improving the academic achievement of slow learner students at the inclusive elementary school level. Students with special needs are slow learners often face significant challenges in learning that have a negative impact on their academic achievement. Through a personalized educational counseling approach, it is hoped that students can develop more effective learning strategies, as well as increase their motivation and self-confidence. This research uses a case study method with the subject of one slow learner student in an inclusive Labuhan 1 State Elementary School. Data was collected through observation, interviews and analysis of academic documents before and after the educational counseling intervention. The research results showed a significant increase in students' academic achievement after receiving intensive educational counseling. These findings indicate that personalized educational counseling can be an effective intervention in supporting the academic development of slow learner students in inclusive environments. The implication of this research is the need to implement special and focused educational counseling services in the inclusive education system to help slow learner students achieve their academic potential optimally.